A deficiência visual e a aprendizagem da química: reflexões durante o planejamento e a elaboração de materiais didáticos táteis - Marques, Natália Pereira (2018)
The inclusion of students with visual impairment in regular education is a topic that has been widely discussed and studied today. People with visual impairment have the right to be active subjects in society and perform their activities without any loss due to their specificity. Thus, the school environment can and should be a space where the student can exercise this right. For this to happen, it is necessary that the school and the professionals who work in it be able to attend these students, so that they will have the same opportunities to learn as the other students. However, when it comes to the teaching of chemistry, as analyzed in our research, it is noted that teachers feel insecure to teach for these students, even on account of insufficient initial training in the field of special education. With this, it is up to the educators to seek new knowledge, in order to minimize these difficulties. One of the objectives of this research is the production of tactile materials that help Chemistry teachers to reflect on certain concepts, making them more meaningful for students with visual impairment. The results obtained with the elaboration of the educational product show that teachers should seek continuous training to feel more secure in order to make their classes more inclusive, developing greater competence to take into account the specificities of their students.